Relations école-familles immigrantes à l’école franco-albertaine : perspectives des travailleurs en établissement en école - Marianne Jacquet; Gwenaëlle André (Recherches en Éducation)
In recent years, Francophone schools in Alberta, a province in western Canada, have seen significant ethno-cultural diversification of their school population, thus reflecting recent migratory changes in Canada. The school population of a Francophone school board located in an agglomeration of Alberta reflects these new migratory trends. A partial ethno-demographic portrait carried out in 2003 in six of its schools indicates that 50% of the pupils come from an immigrant background and come from 23 different countries; mostly from sub-Saharan African countries. This demographic reality, confirmed more than a decade later, represents a major structural change for Francophone schools. In Alberta, as in other Canadian provinces, inclusion is at the heart of discourse and educational practices. With a transformative aim, it intends to promote ethno-cultural diversity in the classroom and equal opportunities through school equity practices. This article focuses on the Settlement workers in schools responsible for bridging family, community and school cultures. The analysis of the interviews of the four workers sheds light on and questions both the institutional practices and the personal strategies put in place to face the challenges encountered in this tripartite collaboration.